A real-time R-wave detection method for wireless ambulatory ECG telemetry. (2015) - Dai, Chenchen; Deng, Yan; Chen, Feifan
Wireless ambulatory ECG telemetry has been widely used in heart rate monitoring in altered gravity conditions, evaluation of high pressure nervous syndrome (HPNS), etc. Comparing with resting ECG monitoring in the hospital, ambulatory ECG features motion artefacts caused by limb movements, including peak interference, instantaneous distortion and amplitude saltation of QRS complex. Beside, in wireless networks, packets are probably dropped because of RF range interference and complex testing environment. To solve these problems, the paper proposes a novel real-time R-wave detection method for wireless ambulatory ECG telemetry (DET). Three sequences of ambulatory ECG were measured and analysed by a custom-made bioelectricity wireless telemetry system. The overall sensitivity, positive predictivity and failed detection were 99.7%, 99.9% and 0.47%, respectively.